Electrically enhanced graphene-metal plasmonic antenna for infrared sensing - Ullah, Z. (Elsevier GmbH, 2021)
An optical graphene-metal hybrid antenna geometry, permitting the efficient tuning of plasmon resonance with unity absorption is reported. The total optical absorption and optical field enhancement are accomplished by designing a graphene-metal antenna. The antenna is comprised of gold hexagon radiator with bilayer graphene on the top, functioning as a double plasmonic resonant structure. The tunability of absorption and optical field enhancement is realized by electrical gating. The strong coupling takes place between the gold plasmons and graphene plasmons, resulting in the strong enhancement of optical fields. The proposed design is modeled in CST Microwave Studio and is simulated through FDTD solver. Moreover, the dynamic tuning of the resonance frequency and optical absorption is achieved by increasing the chemical potential of graphene layers through gate voltage. The tuning range of the designed antenna is optimized in a bandwidth starting from 30 THz to 34 THz. Although at 33 THz the antenna meets matching conditions by having high input impedance, low admittance, and almost unity absorption. The functioning bandwidth of the antenna is preferable for plasmonic applications i.e. infrared sensing and imaging, where high absorption and enhanced field characteristics are required. Â© 2021 Elsevier GmbH